STUDI LITERATUR PROBLEMATIKA PRODUCT DEVELOPMENT DAN STANDARD PRODUK LEMBAGA KEUANGAN DAN PERBANKAN ISLAM - Abdi Jaya; Andri Soemitra; Arbanur Rasyid (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
This research is a literature study that discusses the problems of product development and standards product for Islamic financial and banking institutions. The purpose of this research is to look at the problems faced by financial practitioners and all elements of Islamic banking in order to increase the market share of Islamic banking which tends to be stagnant, where as of October 2019 it only unmoved at 6.01 percent. This study uses literacy methods from various reliable sources, such as research journals, books and so on. The results of the study showed the various problems and challenges faced by Islamic banking in creating product development according to customer interests and satisfaction, both Muslims and non-Muslims and other challenges such as: unsufficient capital, limited human resources who understand Islamic banking, development. products that are in accordance with current technology but still based on Islamic principles and parameters of the maqasid sharia approach, insufficient support from stakeholders related to regulations, socialization of Islamic banking products by academics.